Revising the neotropical genus Americabaetis Kluge, 1992 (Ephemeroptera: Baetidae): phylogenetic classification, new species description, identification tools, and additional records - Marulanda Lopez, Jhon Faber (2024)
Americabaetis is a mayfly genus of Baetidae family widely distributed in the neotropical region. The species are found in diverse habitats, in a broad altitudinal range, and are very abundant in lotic freshwater environments. Currently the genus is composed of 20 species, of which 13 are recorded from South America. The phylogenetic relationships between the species of Americabaetis are unknown, some Argentine species were poorly described and their assignment in the genus remains uncertain. On the other hand, the information of Baetidae and Americabaetis are scattered in the literature and the biological and ecological aspects remain incipiently studied. In addition, we have limited tools to aid in the identification of Americabaetis species by students, non-specialist and specialists. Our aim was to revise the genus Americabaetis and propose a classification for the genus using a phylogenetic hypothesis based on morphological data. Historic and current information of Baetidae and Americabaetis as well as the occurrence maps of the species were compiled in a literature review. A new species from Itatiaia National Park on the borders of Minas Gerais and Rio de Janeiro was described. A machine learning approach using nymphal morphological characteristics to aid in the identification of South American species was proposed as well as an illustrated interactive taxonomic key to identify the nymphs. The monophyly of Americabaetis genus was tested and the relationships among the species of the genus and related genera were hypothesized. A taxonomic classification consistent with the evolution hypothesis of the group was proposed. To finalize, the historic and additional records of Americabaetis from Colombia were updated. Keywords: Baetinae. Phylogeny. Taxonomy. Machine learning.